Using Direct Volume Rendering for Augmented Reality in Resource-constrained Platforms - Cetinsaya, Berk; Neumann, Carsten; Reiners, Dirk (2022 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2022)
Rendering a large volume is a challenging task on mobile and Augmented Reality (AR) devices due to lack of memory space and device limitations. Therefore, we implemented an Empty Space Skipping (ESS) optimization algorithm to render the high-quality large models on HoloLens. We designed and developed a system to visualize the computerized tomography (CT) scan data and Digital Imaging and Communications in Medicine (DICOM) files on Microsoft HoloLens 2. We used the Unity3D game engine to develop the system. As a result, we achieved about 10 times more frames per second (fps) on a high-quality model than the non-optimized version.